Papers - Determination of Oxygen in Alloy Steels and Its Effect upon Tube Piercing (With Discussion) - Newell Hamilton (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1934)
Some years ago, in the manufacture of seamless tubing from an alloy steel containing 0.07 per cent maximum carbon, 18 per cent chromium and 8 per cent nickel, at the plant of The Babcock & Wilcox Tube Co., a peculiar type of piercing defect was noticed. This defect was definitely associated with certain heats of the alloy and was independent of any of the variables of mill operation and billet-heating condition. A thorough analysis of the defective material yielded but one clue to the reason for its abnormal behavior in piercing and that was its oxygen content as determined by the vacuum fusion method. The oxygen content of the defective 18-8 alloy was found to be from two to three times that of the material that had pierced satisfactorily, and this incited an active interest in the vacuum fusion method for the analysis of alloy steels. After a critical survey of the literature on this subject, and considerable experimentation, an apparatus and technique were evolved that gave a fairly rapid, simple and reliable method of analysis. Samples selected from six years of tube production of 18-8 and other corrosion-resistant alloys were analyzed by this method. This paper describes the procedure and gives a correlation of the oxygen, hydrogen and nitrogen contents of a number of alloy steel samples representative of good and bad tube-piercing quality. The Apparatus Basically the apparatus used in this work was that of Jordan and Eckman,' employing a high-frequency induction furnace and the gravimetric method of analyzing the evolved gases, nitrogen being excluded from the determination. In addition, a magazine-type cap and a large-